Tinjauan Waktu Pengembalian Berkas Rekam Medis Pasien Covid Di Rumah Sakit Sumber Waras - Dede Lisda Nurjanah Dede Lisda Nurjanah; Daniel Happy Putra; Puteri Fannya; Deasy Rosmala Dewi (Yayasan Literasi Sains Indonesia, 2022)
The return of patient documents is a component part that has a role for medical records. Standard Operating Procedures (SOP) for Sumber Waras Hospital for the standard time for returning patient documents is 1 x 24 hours after the patient is declared home. The return of patient documents at the Sumber Waras Hospital in March - April 2021 for Covid patients is known from 80 medical record documents the rate of inaccuracy of returns is 25 (31.25%). So the reason for this research is to find out the timeliness of returning the medical record documents of Covid patients at Sumber Waras Hospital. This research uses quantitative descriptive method. The sample in this observation was obtained from the length of time the medical record was returned to the medical record unit. Sampling using Simple Random Sampling. Information was collected using checklists, expedition books and interview guides. The factor causing the inaccuracy of the medical record documents for Covid patients at the Sumber Waras Hospital is the 5M component with the delay in returning medical records. This problem will cause delays in services for Covid patients who will carry out re-control. Therefore, it is necessary to disseminate the Standard Operating Procedure (SOP), with the aim that the reporting of patient medical data can run well.